Change management and advanced wireless network implementation: Detection of monetization opportunities and challenges - Rodrigues, R.; Ferreira, F.; Milici, A.; Carayannis, E.; Ferreira, J. (IEEE Transactions on Engineering Management, 2024)
This study focuses on the interconnection between two topics: change management and advanced wireless networks. Advanced wireless networks can generate turmoil at the deepest level of all sectors of activity by offering the possibility of new connectivity through these networks’ assets, which would require new business models and introduce novel features into purchasing processes and consumer experiences. In addition, telecommunications companies play a fundamental role in developing and implementing these new technologies to ensure they fulfil their promise. Change management practices are critical to ensuring successful advanced wireless network implementation, especially at a strategic and operational level. This research sought to contribute to a more holistic view of the interconnections between these two topics. The multiple-criteria decision analysis approach was used to conduct analyses of the relationships between the associated monetization opportunities and challenges, which included applying the decision-making trial evaluation laboratory technique to clarify their cause-effect links. A multidisciplinary expert panel was recruited to facilitate the method's application. The insights obtained during two panel meetings allowed the proposed process-oriented approach to assist decision makers in analyzing monetization opportunities and challenges related to advanced wireless network adoption according to the following five clusters: service offer; vendor value proposition; operational management; strategic management; and external factors. Contributions and limitations are also examined.